1994
DOI: 10.1111/j.1741-2358.1994.tb00102.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Salinum on the symptoms of dry mouth: a pilot study

Abstract: The effect of a new saliva substitute, Salinum, was tested in 37 patients with severe symptoms of reduced salivation. The majority of the patients had suffered from hyposalivation and dry mouth for more than 8 years. The saliva substitute consisted of a water soluble extract of linseed. The physical properties of this extract are similar to those of the glycoproteins of the salivary secretions. The patients used the saliva substitute for a seven days period. Prior to the use of the extract the patients reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…For ten patients from the postradiation group (14 patients), the symptoms of xerostomia decreased significantly. Some patients reported particular relief during the night; the symptoms taste, speech, chewing, and swallowing were reduced to a varying degree [45]. As no control groups were included in this study, these results have to be interpreted with caution.…”
Section: Clinical Performancementioning
confidence: 82%
“…For ten patients from the postradiation group (14 patients), the symptoms of xerostomia decreased significantly. Some patients reported particular relief during the night; the symptoms taste, speech, chewing, and swallowing were reduced to a varying degree [45]. As no control groups were included in this study, these results have to be interpreted with caution.…”
Section: Clinical Performancementioning
confidence: 82%
“…Three studies assessed linseed fluid used ad libitum for 1-and 3-week periods post-irradiation and found that it reduces xerostomia [135][136][137]. Also, it was noted that the effect tended to increase with increasing time of use of the fluid (during a 3-week period) [135], that generally the patients with the most severe symptoms experienced the greatest relief [137], and that linseed fluid was preferred to CMC fluid [135].…”
Section: Gustatory and Masticatory Stimulationmentioning
confidence: 95%
“…Also, it was noted that the effect tended to increase with increasing time of use of the fluid (during a 3-week period) [135], that generally the patients with the most severe symptoms experienced the greatest relief [137], and that linseed fluid was preferred to CMC fluid [135].…”
Section: Gustatory and Masticatory Stimulationmentioning
confidence: 98%
“…Elles sont présentées sous différentes formes galéniques (liquide, pastille ou chewinggum). On trouve également dans le commerce d'autres substituts salivaires comme l'oxyde de polyéthylène [22] ou des extraits de polysaccharides provenant de graines de lin [23]. Le premier semble plus efficace que la méthylcellulose pour réduire les symptômes de xérostomie, le second donne des résultats satisfaisants chez environ 75 % des patients.…”
Section: Traitementunclassified